2013
DOI: 10.9799/ksfan.2013.26.4.879
|View full text |Cite
|
Sign up to set email alerts
|

Quality Characteristics of Muffins containing Akebia quinata Leaves Powder

Abstract: This study investigates the quality characteristics of muffins prepared with various concentrations of akebia leaves powder. Muffins are prepared by additions of 0%, 2%, 4%, 6% and 8% powder to the flour for basic formulation. Heights decrease significantly when the amount of Akebia leaves powder increases. When the weight is being measured, there are no meaningful differences between the samples. As a result from measuring the colors, the lightness, redness and yellowness of muffins decrease as the concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 17 publications
(1 reference statement)
1
0
0
Order By: Relevance
“…This phenomenon also affected the volume and height of the muffins. In corroboration with this finding, Lee et al () reported a reduced volume and height of muffins when flour was replaced by other ingredients.…”
Section: Resultssupporting
confidence: 52%
“…This phenomenon also affected the volume and height of the muffins. In corroboration with this finding, Lee et al () reported a reduced volume and height of muffins when flour was replaced by other ingredients.…”
Section: Resultssupporting
confidence: 52%